The Comparative and Usefulness of Platelet Distribution Width in Acute Coronary Syndrome - Idar Mappangara; Ali Aspar Mappahya; Sheila Witjaksono (The Indonesian Biomedical Journal, 2016)
BACKGROUND: Identifying risk factors for acute coronary syndrome (ACS) is important for both diagnostic and prognostic purposes. Abnormal platelet parameters, mainly platelet count (PC), mean platelet volume (MPV) and platelet distribution width (PDW) are thought to be among these risk factors because platelet activation plays a pivotal role in ACS. PDW is a more specific marker of platelet activation, since it does not increase during simple platelet swelling. In this study, the comparison of risk factors along with the PDW between Non ST-Elevation ACS (NSTEACS) and ST-Elevation ACS (STEACS) were investigated.METHODS: This is a cross-sectional study, patients with ACS that admitted at dr.Wahidin Sudirohusodo General Hospital Makassar since December 2014 to March 2015 who undergo coronary angiography were enrolled. All data variables were taken according to the medical record. PDW was taken on first blood examination at hospital admission. Data was significant if p-value <0.05 and was processed with SPSS version 16.RESULTS: A total of 63 patients were enrolled. There were significantly higher PDW (p=0.047) in STEACS group (13.7±2.0 fL) than in NSTEACS group (12.6±2.3 fL). There were a significant positive correlation between PDW value and SYNTAX scores (Pearson, r=0.552, p=0.000). Cardiovascular risk factors such as history of ACS before (p=0.049 & OR=10.216) and dyslipidemia (p=0.049 & OR=3.915) along with PDW (p=0.003 & OR=1.733) were significant predictor of the incidence of multivessel disease in patient with ACS.CONCLUSION: An increased PDW may predicting more severe disease in ACS based on incidence of STEACS and multivessel disease more often and higher SYNTAX score.KEYWORDS: platelet distribution width, PDW, acute coronary syndrome, ACS, multivessel disease, SYNTAX